2012
DOI: 10.1002/jbmr.1718
|View full text |Cite
|
Sign up to set email alerts
|

High serum sclerostin predicts the occurrence of osteoporotic fractures in postmenopausal women: The center of excellence for osteoporosis research study

Abstract: Sclerostin regulates bone formation by inhibiting Wnt pathway signaling. Low circulating sclerostin levels cause high bone mass. We hypothesized that postmenopausal women with increased sclerostin levels have a greater risk for osteoporosis-related fractures. We examined the association between circulating sclerostin together with bone turnover markers and osteoporosis-related fracture risk in 707 postmenopausal women, in a population-based study with a mean follow-up period of 5.2 AE 1.3 years. Multivariate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
5
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 37 publications
7
98
5
2
Order By: Relevance
“…The latter is consistent with the data reported by Gennari et al (16) using DXA, although an association between sclerostin serum levels and DXA measurements was also described in T1DM (17). Besides BMD, in previous works, sclerostin was associated with fracture risk, although etherogeneus results were reported (31,32). In particular, sclerostin was related to vertebral fractures in T2DM (33).…”
Section: Clinical Studysupporting
confidence: 91%
See 1 more Smart Citation
“…The latter is consistent with the data reported by Gennari et al (16) using DXA, although an association between sclerostin serum levels and DXA measurements was also described in T1DM (17). Besides BMD, in previous works, sclerostin was associated with fracture risk, although etherogeneus results were reported (31,32). In particular, sclerostin was related to vertebral fractures in T2DM (33).…”
Section: Clinical Studysupporting
confidence: 91%
“…A reduced bone formation as a consequence of reduced osteoblast activity has been identified as the mean pathogenetic effect or for low bone mineral density (BMD) in subjects with T1DM (1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39). intimal thickening in atherosclerosis, and Wnt/b-catenin signaling is a regulator of VSMC behavior (9).…”
Section: Introductionmentioning
confidence: 99%
“…SOST has been revealed as a susceptibility gene for osteoporosis and osteoporotic fractures in different populations, including in Chinese [19,20,31,32]. Moreover, a positive correlation has been reported between incident hip fractures and high sclerostin levels [33,34]. In this study, we also find genetic variance of SOST is correlated to skeletal response to alendronate treatment for the first time.…”
Section: Discussionsupporting
confidence: 65%
“…This could be in apparent contradiction with the known impact of sclerostin on post-menopausal osteoporosis [30]. Hence, in post-menopausal women, high serum sclerostin levels predict osteoporotic fractures more than other bone makers [31,32]. Besides, Malluche et al [33] reported that baseline serum sclerostin level correlated with bone mass, but 1-year follow-up showed that high serum sclerostin predicts the loss of more bone mass.…”
Section: Discussionmentioning
confidence: 99%